Interactions, images and texts - Norris, Sigrid (De Gruyter Mouton, 2014)
Includes bibliographical references and index.; This book provides a comprehensive text of current research into multimodality, outlining in-depth delineation of each primary theoretical and methodological approach, as well as personal accounts of scholars, who are responsible for the various approaches' advancements. The book additionally offers a plethora of analysis chapters, written by scholars from across the world, with vastly diverse themes ranging from buying popcorn, protests in Oman, coaching sessions and identity, to kitesurfing, typography, TV news, billboards, workplace practices, or analyzing web pages, Facebook, comic books, and more.Flexible and easy to use, the Reader includes key terms, suggested further readings, and a project idea for each chapter. The key terms for the chapters also comprise the extensive alphabetical glossary